An assessment of efficiency in potential screening for Wilson's disease. Issue 4 (December 1981) - Saito, T
Abstract : The efficiency of screening for Wilson's disease by serum caeruloplasmin determination was assessed by analysing the epidemiologic data of 289 affected families in Japan. The estimated gene frequency was 5.2 x 10(-3). The sensitivity of the screening test was 93% at a proposed cut-off level of 120 mg/l and the specificity was 99.83%. In Japan 1 500 000 children are born every year of whom 50 would be expected to have Wilson's disease. The present analysis of potential screening for all children would grade three of them as false-negatives and identify 2621 as false-positives. An analysis for children only from consanguineous marriages produced a more efficient result, with a much higher predictive value of the positive and case-finding rate. Although the number of patients identified in this latter high-risk screening group was small, it is worth considering as a pilot study.